Association of Socio-Demographic Profile with Prevalence of Multi Drug Resistant Tuberculosis among Retreated Pulmonary Tuberculosis Patients in North India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Methods: An observational cross sectional study, which includes 116 patients of sputum smear positive pulmonary TB of age 18 or above. Further, detailed history taking regarding different demographic profile was done. Also, they were subjected to CB-NAAT and rifampicin resistant cases were considered as MDR-TB.Results: Proportion of MDR-TB was 31.89% among retreatment TB cases. 56.75 % (n=21) of MDR-TB cases were between the age group of 21-40 years. Proportion of MDR-TB was higher among males (75.67%), married (59.45%) and rural dwellers 59.45%. Proportion was 61.76% among patients with BMI